Studies of In Vitro Activities of Voriconazole and Itraconazole against Aspergillus Hyphae Using Viability Staining - Lass-Flörl, Cornelia (American Society for Microbiology, 2001)
The minimal fungicidal concentrations (MFCs) of voriconazole and itraconazole for five clinical isolates each of Aspergillus terreus, Aspergillus fumigatus, Aspergillus flavus, and Aspergillus niger were determined by a broth macrodilution method. Conidial suspensions as inocula were compared to hyphae as inocula since the invasive form of aspergillosis is manifested by the appearance of hyphal structures. In addition, cell viability staining with the dye FUN-1 was performed to assess time-dependent damage of hyphae exposed to various concentrations of the antifungal agents. With conidial inocula the MFC ranges of voriconazole were 0.5 to 4 μg/ml and those of itraconazole were 0.25 to 2 μg/ml, whereas the MFCs (2 to >16 μg/ml) with hyphal inocula were substantially higher (P < 0.01) for both itraconazole and voriconazole. Only minor differences between the tested antifungals were observed since 16 of 20 and 17 of 20 of the isolates of Aspergillus spp. tested appeared to be killed by voriconazole and itraconazole, respectively. The results of FUN-1 viability staining correlated closely to colony counts, but various time- and dose-dependent levels of viability of hyphae were also observed. In conclusion, our study demonstrates the importance of the type of inoculum used to test antifungals and the applicability of FUN-1 staining as a rapid and sensitive method for assaying the viability of hyphae.